Development of Mental Imagery Program Based on Mirror Neuron Theory for Enhancing Phonological Working Memory of Primary School Students: Electroencephalogram Study - Wanichaya Jairew , Parinya Ruangtip , Sirikran Juntapremjit (South Eastern European Journal of Public Health, 2025)
Phonological Working Memory (PWM) is an important part of language functions and learning because it stores and processes sound or spoken information temporarily. Recent studies have shown that mirror neurons (MN) and mental imagery (MI) can help improve PWM effectiveness. The goal of this study is to investigate the P300 brain wave and come up with a theory about a mirror neuron-based mental imagery training program that can help the phonological working memory in primary school students. We think that mirror neurons, which are activated when we observe and imitate, can improve PWM. Mental imagery, on the other hand, makes it easier to store and organize verbal information by creating auditory representations, which supports the mental processes that support working memory. The results show that using the mirror neuron theory-based mental imagery training program makes PWM work better. This is shown by the P300 event-related potential (ERP), which has a shorter latency and higher amplitude, which means better cognitive processing in the phonological domain.